2014
DOI: 10.1016/j.sbspro.2014.12.467
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Concerns about Genetically Modified (GM) Food Consumption using the Theory of Planned Behavior (TPB)

Abstract: The commercial use of genetic modification (GM) technology in the food industry has been a common issue in the public. Decision-makers and scholars have indicated the benefits of the application of GM technology to the agriculture and food industries, such as lower production costs and product development with regard to sensory-related factors, health, and convenience that increase farming productivity, food supplies, and efficiency and reduce prices. However, previous studies have indicated that there is limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 11 publications
(17 reference statements)
1
15
0
Order By: Relevance
“…For example, prior research has reported that consumer perceptions of benefits and risks are considered to be major precursors of their attitudes towards GM food (Bredahl et al, 1998) and, thus, influence its adoption (Smyth et al, 2015). Kim (2014) provided empirical evidence that consumers' attitudes, social influences (subjective norms) and situational influences (perceived behavioural control [PBC])…”
Section: Discussionmentioning
confidence: 99%
“…For example, prior research has reported that consumer perceptions of benefits and risks are considered to be major precursors of their attitudes towards GM food (Bredahl et al, 1998) and, thus, influence its adoption (Smyth et al, 2015). Kim (2014) provided empirical evidence that consumers' attitudes, social influences (subjective norms) and situational influences (perceived behavioural control [PBC])…”
Section: Discussionmentioning
confidence: 99%
“…This study used the six-item GMF knowledge scale from the literature [ 9 , 30 ] (e.g., “When it comes to GM food, I don’t know a lot”), which were measured on a 5-point Likert-type scale (1 = strongly agree, 5 = strongly disagree).…”
Section: Methodsmentioning
confidence: 99%
“…Addressing the growing concern for global food security and the challenge to feed nine billion inhabitants of this planet by 2050, GMF has been a recent advancement of food-based technologies [ 9 , 10 ]. Besides, more than two billion people globally are combating malnutrition due to vitamin and mineral deficiencies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of food consumption (Kim, 2014), ecological concern refers to the concern about doing the right thing for animal welfare, the environment, and the ecosystem, which can be regarded as moral norms. Human should respect the environment via environmental ethics and beliefs and ensure the ethical connection between humans and the environment.…”
Section: Environmental Ethicsmentioning
confidence: 99%